If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3j + -10 = 50 Reorder the terms: -10 + 3j = 50 Solving -10 + 3j = 50 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '10' to each side of the equation. -10 + 10 + 3j = 50 + 10 Combine like terms: -10 + 10 = 0 0 + 3j = 50 + 10 3j = 50 + 10 Combine like terms: 50 + 10 = 60 3j = 60 Divide each side by '3'. j = 20 Simplifying j = 20
| (-2x-3)(2x-1)=(x+4)(2x-1) | | (x+2)+(3x-2)+(2y+1)+(2x-3)=360 | | 2v+3= | | 12m+144= | | 10x+0.5y+0.25z=100 | | 8.4+10= | | 2k-5=30 | | -35+9s=-4(5s-3) | | 11+2x-14=8x-3-6x | | (2w^3r^-2/5w^-2rz) | | 5+9x=5+12x-3x | | 10x-(7x+4)=8x | | 8x-4-2x=6x-4 | | -5(3-4a)=20 | | 1y=4x+283 | | 91375193459137451057+73452863568283456345384-661649589246861356218565= | | 6+2x=4x+8 | | 18x^2+8x-1=0 | | 26.6=1+0.25 | | 21=-5(7x+8) | | 2(2x+3)=21-3(x-2) | | 6(4w+8)=28 | | 4(4w+3)=5 | | -5(2t+6)=30 | | -10(s+2)=-14 | | 3x/4-1/3=1-2/3(x-1/6) | | -1(c-9)=12 | | 0.60000001+-3= | | 3x+4x*8x=9 | | .40(x+300)=.10(300)+.50x | | -10(s+2)=55 | | -6-4(1-2b)=22 |